Pengembangan Media Pembelajaran Interaktif untuk Ranah Kognitif pada Mata Pelajaran Sistem Komputer di Kelas X Teknik Komputer dan Jaringan SMK Negeri 3 Malang dengan Model Pengembangan 4D - Laras Krisnayuwati Suwardi; Admaja Dwi Herlambang; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
SMKN 3 Malang is a Vocational High School that provides competency in Computer and Network Engineering expertise. Problems encountered in learning activities are in the cognitive domain, where the daily tests of 36 students in class X Computer and Network Engineering SMKN 3 Malang get an average value of 56.89 in Computer System lessons with Basic Competence material 3.4 and 4.4, which is not complete because it is not sufficient Minimal Completeness Criteria. Based on the problems found, it is necessary to develop an Interactive Learning Media. The study was conducted using the 4D development model through 4 stages, namely define, design, develop, and disseminate. The subjects of this study were students of class X Computer and Network Engineering SMKN 3 Malang. Data obtained through observation, interviews, questionnaires, and tests for pretest and posttest. The results of the validation of material experts get a percentage of 98.00% (Very Good), the validation of media experts get a percentage of 60.00% (Good), the results of student responses get a percentage of 93.40% (Very Good). The average pretest produced a value of 55.83, the average posttest produced a value of 87.63, and the different test produced a significance of 0.00 (sig â‰¤ 0.05). Based on the increase in the average value of pretest and posttest of 31.8 and the results of the effectiveness test carried out, so it can be concluded that the developed Interactive Learning Media is proven to assist students in improving learning outcomes in the cognitive domains.